The Requirement Analysis of the IoT-Based Vehicular Spatial Allocation System - K., Swapna; G., Sloka; K. Varanitha, Reddy; G., Nikhila; P., Manisha (INTI International University, 2025)
Today’s crowded cities often have trouble with parking. More cars are driving than there are places to park. Because of this, effective parking management systems are now required. Consequently, we exhibit the benefits of an IoT-based parking management system for efficiently managing parking spaces. To illustrate how it works, we put in IR sensors for sensing if the spot is taken and message to a DC motor that opens the gate. Currently, internet connectivity is handled by a Wi-Fi modem, and the AVR microcontroller runs the entire system. IOT Gecko supports our project by providing online connectivity and designing an IOT management graphical user interface. IR sensors allow the system to spot if parking slots are currently in use. After reading the available parking slot number, the system notifies the cloud server and lets people verify the available slots online. As a result, people can find free parking spots online from any place and not worry about rushing. OpenBay, as a result, solves the parking shortage for cities and gives users a smart parking management system based on IoT.